Cross-sectional study on the role of public awareness in preventing the spread of COVID-19 outbreak in India. Issue 1154 (10th September 2020) - Kaushik, Manish; Agarwal, Divya; Gupta, Anil K
ABSTRACT: Background: WHO has recommended personal hygiene (respiratory hygiene, using face masks, washing hands with warm water and soap, use of alcohol-based hand sanitizers, avoid touching mouth, eyes & nose, cleanliness), social distancing and careful handling of purchased products as an effective preventive measure for COVID-19 disease. The growing pandemic of COVID-19 disease requires social distancing and personal hygiene measures to protect public health. But this message is not clear and well understood among people. The aim of this study is to determine the awareness, knowledge and attitude about COVID-19 and relate the behaviour of Indian society, especially when the country is restarting all its economic activities, after the complete lockdown. Method: The present paper is based on an extensive survey among 21 406 adult participants of various sections of Indian society with different age groups between 18 and 80 years to introspect the level of public awareness with respect to cause, spread, prevention and treatment of disease caused by spread of COVID-19 viral outbreak, which will be automatically reflected in the societal behavioural response of rigorous precautionary measures. Conclusions: There is a need to extend the knowledge base among individuals to enhance their active participation in the prevention mechanisms with respect to the spread of the pandemic. There is a need to elaborate the Indian socio-cultural aspects, so that society starts appreciating and voluntarily following social distancing. This should improve the adaptability of people with livelihood resilience to let them protect themselves not only from the present pandemic but also from all other unforeseen infections, and to provide care to patients.